2021
DOI: 10.1002/csc2.20355
|View full text |Cite
|
Sign up to set email alerts
|

Differences among eighteen winter pea genotypes for forage and cover crop use in the southeastern United States

Abstract: Winter pea (Pisum sativum L.) can be used as a forage and cover crop in the southeast and mid-Atlantic United states; however, minimal effort has been devoted to optimize winter pea genetics for forage and cover crop production in these regions. Studies were conducted from 2015-2017 in Maryland and North Carolina screening 18 winter pea genotypes for forage and cover crop use. Winter pea genotypes were compared with widely grown crimson clover (Trifolium incarnatum L.) and hairy vetch (Vicia villosa Roth]. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In recent studies in Nebraska pre‐harvest broadcast hairy vetch produced 0.36–0.54 when terminated by early May in eastern sites (Koehler‐Cole & Elmore, 2020) and 0.81 Mg ha –1 when drill‐planted by September and terminated in May in drier, western sites (Rosa et al., 2021). Winter pea is less cold hardy than hairy vetch (Vann et al., 2021) but cultivars suitable to Nebraska produced 0.7 Mg ha −1 biomass in dryland and 2.74 Mg ha −1 in irrigated conditions by mid‐June (Homer et al., 2019). Legumes may become more attractive cover crops due to the current high fertilizer prices, but to achieve greater biomass and N 2 fixation, growers need to improve legume management.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies in Nebraska pre‐harvest broadcast hairy vetch produced 0.36–0.54 when terminated by early May in eastern sites (Koehler‐Cole & Elmore, 2020) and 0.81 Mg ha –1 when drill‐planted by September and terminated in May in drier, western sites (Rosa et al., 2021). Winter pea is less cold hardy than hairy vetch (Vann et al., 2021) but cultivars suitable to Nebraska produced 0.7 Mg ha −1 biomass in dryland and 2.74 Mg ha −1 in irrigated conditions by mid‐June (Homer et al., 2019). Legumes may become more attractive cover crops due to the current high fertilizer prices, but to achieve greater biomass and N 2 fixation, growers need to improve legume management.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, winter pea has been found to be a potential winter legume cover crop for the Southeast, and the regional breeding programs are now focusing on improving its adaptability (Vann et al., 2019, 2020). Crimson clover and hairy vetch are both commonly used legume cover crops in the southeastern United States and are popular for their high biomass production (Vann et al., 2016, 2021). However, when used as a sole crop, crimson clover can have notably slower N release than other legume cover crops and can even lead to N immobilization (Reberg‐Horton et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hairy vetch is a legume cover crop grown as a N source, weed suppressor, topsoil conditioner, and erosion reducer (Clark, 2012;Vann et al, 2019). Austrian winter pea is another legume that is grown as a plow-down N source, weed suppressor, and forage (Clark, 2012;Vann et al, 2019Vann et al, , 2021. Brassicas such as radish and turnip produce large taproots that can penetrate deep soil layers ("bio-drilling"), alleviate compaction, scavenge nutrients from deep in the soil profile, and provide macrochannels that facilitate water infiltration (Clark, 2012;Saini et al, 2005).…”
Section: Core Ideasmentioning
confidence: 99%
“…(2017) reported that growers want future cover crop breeding to focus on traits such as winter hardiness, early vigor, and weed suppression in grass species and improving biological nitrogen fixation (BNF) in legume species. Many efforts are ongoing in grasses to improve these agronomic characteristics (Ayalew et al., 2018; Brasier et al., 2019), while large gaps remain on BNF improvement of legume cover crops (Vann et al., 2021).…”
Section: Introductionmentioning
confidence: 99%